2022
DOI: 10.3390/polym14132749
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Immobilised Catechol-Based Hypercrosslinked Polymer as Heterogeneous Fenton Catalyst for Degradation of Methylene Blue in Water

Abstract: Clean water is one of the sustainable development goals. Organic dye is one of the water pollutants affecting water quality. Hence, the conversion of dyes to safer species is crucial for water treatment. The Fenton reaction using Fe as a catalyst is a promising process. However, homogeneous catalysts are normally sensitive, difficult to separate, and burdensome to reuse. Therefore, a catechol-based hypercrosslinked polymer (catechol-HCP) was developed as an inexpensive solid support for Fe (catechol-HCP-Fe) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Similarly, catechols are widely used ligands in coordination chemistry, their redox “non‐innocent” properties have been thoroughly explored in catalysis [21,22] . Furthermore, recent studies have shown that metal/catechol species can be efficiently immobilized onto MOF [23–29] and POP [30–35] supports, with applications in hydrogenation, hydrosilylation or catalytic degradation of toxic organophosphate compounds [14] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, catechols are widely used ligands in coordination chemistry, their redox “non‐innocent” properties have been thoroughly explored in catalysis [21,22] . Furthermore, recent studies have shown that metal/catechol species can be efficiently immobilized onto MOF [23–29] and POP [30–35] supports, with applications in hydrogenation, hydrosilylation or catalytic degradation of toxic organophosphate compounds [14] …”
Section: Introductionmentioning
confidence: 99%
“…[7,8,[14][15][16][17][18][19][20] Similarly, catechols are widely used ligands in coordination chemistry, their redox "non-innocent" properties have been thoroughly explored in catalysis. [21,22] Furthermore, recent studies have shown that metal/catechol species can be efficiently immobilized onto MOF [23][24][25][26][27][28][29] and POP [30][31][32][33][34][35] supports, with applications in hydrogenation, hydrosilylation or catalytic degradation of toxic organophosphate compounds. [14] Herein, we report the synthesis of novel porous macroligands made of redox-active catechol moiety as co-monomer in polymeric matrixes (namely CatMP-1) and their subsequent metalation with Cu cations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the material HCPs, the catalytic activity and stability of the immobilized precious metal were signi cantly improved, because of its organic cage frameworks and the coordination between the heteroatoms in HCPs and metal ions, which could x the ultra-ne metal nanoparticles in the cages and make the metal particles rmly anchored to maintain an excellent activity in the long term, as well as serving as a catalyst support for the production of heterogeneous catalytic converters. [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They are becoming more popular, especially for selective adsorption uses, because of their cost-effectiveness, ability to have their pore structure tuned, and ease of synthesis . HCPs have been demonstrated to be effective adsorption candidates for a variety of chemical species, including cations, anions, and organic compounds. The application of HCPs in the field of iodine adsorption has gained significant interest since Pastukhov and co-workers employed magnetic iron oxide nanocomposites incorporating polystyrene-based HCPs for iodine adsorption. This primary finding suggested that the porosity of the HCP component could increase the adsorption effectiveness of the composites .…”
Section: Introductionmentioning
confidence: 99%